Water temperature affects aggressive interactions in a Neotropical cichlid fish - Brandão, Manuela L. [UNESP]; Colognesi, Gisele [UNESP]; Bolognesi, Marcela C. [UNESP]; Costa-Ferreira, Roselene S. [UNESP]; Carvalho, Thaís B.; Gonçalves-de-Freitas, Eliane [UNESP] (FapUNIFESP (SciELO), 2018)
Changes in water temperature may affect the aggressive behavior of aquatic organisms, such as fish, either by changing some physiological mechanisms or by increasing the probability of encounters between individuals as a result of variation in their swimming activity. In our study, we evaluated the influence of increasing and decreasing temperature on the aggressive behavior of the Neotropical cichlid fish Cichlasoma paranaense. Firstly, we tested the critical thermal maximum (CTMax) tolerated by this species. Then, we tested the effect of decreasing or increasing the water temperature in 6o C (starting at 27° C) on the aggressive interactions of fish under isolation or housed in groups. We found a CTMax value of 39° C for C. paranaense. We also observe that a 6° C decrease in water temperature lowers swimming activity and aggressive interactions in both isolated and group-housed fish, as expected. On the other hand, the increase in temperature had no effect on the fish’s aggressive behavior, neither for isolated nor for grouped fish. We concluded that C. paranaense shows high tolerance to elevated temperatures and, in turn, it does not affect aggressive behavior. Nevertheless, we cannot dismiss possible effects of elevated temperatures on aggressive interactions over longer periods. Keywords: Agonistic behavior, Critical thermal maximum, Social hierarchy, Social isolation, Thermal environmental changes.
Keywords: Agonistic behavior; Critical thermal maximum; Social hierarchy; Social isolation; Thermal environmental changes